Advertising strategy and contract coordination for a supply chain system: immediate and delayed effects - Yu, Hui; Yang, Wei; Xu, Na; Du, Yang (Kybernetes, 2023)
PurposeAfter receiving advertising messages, most consumers rarely purchase the advertised products at once, which results in a delay between advertising exposure and its effect. This paper is devoted to exploring the advertising decision and coordination issues for a supply chain system subject to advertising immediate and delayed effects.Design/methodology/approachBy applying the game theory, the differential game models with delay are constructed for the supply chain to examine the equilibrium advertising efforts, brand goodwill and the optimal profits under the different cooperation situations. A class of transfer payment contracts is designed to achieve the best outcome of the supply chain. Illustrative examples are given to demonstrate the effectiveness of addressed results and provide some managerial perspectives.FindingsIt can be found that the complete cooperation situation can stimulate the advertising investment, drive the product demand and improve the economic profit. Also, a class of transfer payment contracts is designed in this paper, such that the supply chain can perfectly realize the profit maximization, and each member can achieve the Pareto improvement.Research limitations/implicationsThis work does not address the random market environment, which can be filled in the future. Furthermore, this paper has been done in a single supply chain structure. It is an interesting future line of research when taking competitive behavior (e.g. competition among manufacturers, retailers or supply chains) into account.Practical implicationsThis study will help managers make advertising strategies, advise an optimal cooperation way and design the coordination contracts to ensure the economic development of the supply chain. These obtained conclusions may provide a valuable decision-support for marketing management.Originality/valueFor a supply chain, the most previous literature about dynamic advertising models focused on a single advertising effect-immediate effect. This work explores advertising strategy with double advertising effects and investigates the coordinating power of new transfer payment contracts.